2019
DOI: 10.1186/s13244-019-0689-7
|View full text |Cite
|
Sign up to set email alerts
|

Advanced endoscopic interventions on the pancreas and pancreatic ductal system: a primer for radiologists

Abstract: In recent years, technological advancements including endoscopic ultrasound (EUS) guidance and availability of specifically designed stents further expanded the indications and possibilities of interventional endoscopy. Although technically demanding and associated with non-negligible morbidity, advanced pancreatic endoscopic techniques now provide an effective minimally invasive treatment for complications of acute and chronic pancreatitis. Aiming to provide radiologists with an adequate familiarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Bang et al 27 demonstrated a 100% correlation between CT localization and EUS localization of DDS. Endoscopic ultrasound also provides an opportunity for therapeutic intervention 29 …”
Section: Diagnosismentioning
confidence: 99%
“…Bang et al 27 demonstrated a 100% correlation between CT localization and EUS localization of DDS. Endoscopic ultrasound also provides an opportunity for therapeutic intervention 29 …”
Section: Diagnosismentioning
confidence: 99%
“…3 Indications for percutaneous or endoscopic intervention include management of pancreatic duct leaks or obstruction, symptomatic fluid collections, need for diagnostic tissue biopsy, and bleeding or other vascular complications. [4][5][6] Pancreatic Duct Leak or Obstruction Pediatric pancreatitis can be divided into acute pancreatitis, acute recurrent pancreatitis, and chronic pancreatitis. 7 Etiologies of acute pancreatitis include duct obstruction, drug toxicity, and systemic illness.…”
Section: Pancreatic Disordersmentioning
confidence: 99%
“…Although some terms are often used by various authors and clinicians, terminology and descriptor language has not been standardized[ 35 ]. The most commonly utilized terms to describe abnormalities in literature are: Disruption (some authors dived into partial/incomplete and total/complete disruptions), disconnection, DPDS, transected, leak, fistula, rupture, stricture, stenosis, cut-off, obstruction and communication/non-communication with collection[ 9 , 13 , 14 , 18 , 19 , 22 , 36 - 40 ]. This heterogeneity may lead to confusion when reporting and interpreting data[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The complete disruption of the MPD is one of two necessary conditions to diagnose DPDS. An image study showing a functional pancreatic tissue upstream to the complete disruption is necessary to define DPDS[ 11 , 40 ]. Therefore, ERCP alone cannot appropriately describe this phenomena; however, when pancreatography is performed by MRCP it is possible to diagnose DPDS since it allows study the MPD upstream the disruptions and the pancreatic tissue[ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation